2011
DOI: 10.1017/s0950268811000793
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzaetype b infection, vaccination, andH. influenzaecarriage in children in Minnesota, 2008–2009

Abstract: An increase in invasive Haemophilus influenzae type b (Hib) cases occurred in Minnesota in 2008 after the recommended deferral of the 12-15 months Hib vaccine boosters during a US vaccine shortage. Five invasive Hib cases (one death) occurred in children; four had incomplete Hib vaccination (three refused/delayed); one was immunodeficient. Subsequently, we evaluated Hib carriage and vaccination. From 18 clinics near Hib cases, children (aged 4 weeks-60 months) were surveyed for pharyngeal Hib carriage. Records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Because conjugate vaccines also reduce pharyngeal carriage ( 4 ), concerns have been raised that other H. influenzae strains could fill the ecologic niche and result in invasive disease (serotype replacement) ( 5 ), although no studies have demonstrated increased carriage rates of other H. influenzae serotypes after routine Hib vaccination ( 6 ). Some countries have reported small but significant increases in invasive ncHi disease after routine Hib vaccination ( 7 10 ); others have not ( 11 , 12 ).…”
mentioning
confidence: 99%
“…Because conjugate vaccines also reduce pharyngeal carriage ( 4 ), concerns have been raised that other H. influenzae strains could fill the ecologic niche and result in invasive disease (serotype replacement) ( 5 ), although no studies have demonstrated increased carriage rates of other H. influenzae serotypes after routine Hib vaccination ( 6 ). Some countries have reported small but significant increases in invasive ncHi disease after routine Hib vaccination ( 7 10 ); others have not ( 11 , 12 ).…”
mentioning
confidence: 99%
“…The hpd assay is highly specific for H. influenzae and provides a potential tool to differentiate H. influenzae from H. haemolyticus, including nonhemolytic H. haemolyticus. In this study, both hpd and fucK PCR assays were evaluated against 16S rRNA gene phylogeny for distinguishing H. influenzae from H. haemolyticus by the use of Haemophilus isolates identified during a carriage study in Minnesota (12,22 All isolates were further characterized using the hpd and fucK PCR assays with crude DNA as the template (28). All of the 31 hemolytic H. haemolyticus and 128 other Haemophilus species isolates were negative by both hpd and fucK PCR assays.…”
mentioning
confidence: 99%
“…The indicator vaccination rate is often used interchangeably with vaccine coverage in the research literature, but is rarely explicitly defined. 9,20,[26][27][28]32,38,[41][42][43][44] It is usually synonymous with coverage, e.g. "the vaccination rates are calculated from the numbers of vaccinated persons over the respective populations" 7 or in a paper by Ernst et al, 45 where they state that changes in vaccination coverage by region are reported as vaccination rate per 100,000 children.…”
Section: Vaccination Ratementioning
confidence: 99%